2005
DOI: 10.1079/bjn20041331
|View full text |Cite
|
Sign up to set email alerts
|

Bone status in an animal model of chronic sub-optimal nutrition: a morphometric, densitometric and mechanical study

Abstract: In children, inappropriate eating habits can induce a disease known as nutritional dwarfing (ND). Due to the link between nutritional condition and bone growth, the effects induced by a 20 % reduction of food intake on bone competence were assessed in an animal model of ND. Bone status during catch-up growth was also analysed. Male Wistar rats were divided into control (C) and ND groups. C rats were fed ad libitum. ND received 80 % of the diet consumed by C for 4 weeks (T4); thereafter, they were fed ad libitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
1
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 28 publications
4
34
1
9
Order By: Relevance
“…Undernutrition (in response to either food restriction or exposure to hypoxia), which mainly affects protein and energy availability, affects bone biomechanical properties (21,29,(32)(33)(34)(35)(36) in growing rats by adapting the growth of the bone mass to that of the body mass. Bone mechanical quality of a whole bone (structural properties) depends on the integration of the 'mechanical quality of the mineralised tissue' (material stiffness mainly associated with collagen mineralisation) and the 'architectural quality of the structural bone design' (shape, size, architectural distribution of mineralised tissue) (37) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Undernutrition (in response to either food restriction or exposure to hypoxia), which mainly affects protein and energy availability, affects bone biomechanical properties (21,29,(32)(33)(34)(35)(36) in growing rats by adapting the growth of the bone mass to that of the body mass. Bone mechanical quality of a whole bone (structural properties) depends on the integration of the 'mechanical quality of the mineralised tissue' (material stiffness mainly associated with collagen mineralisation) and the 'architectural quality of the structural bone design' (shape, size, architectural distribution of mineralised tissue) (37) .…”
Section: Discussionmentioning
confidence: 99%
“…Both NxGR and HxC rats also have in common important changes in the mechanical properties of the appendicular skeleton. Biomechanical tests performed on femur diaphyseal shafts (21,23) revealed a lower than normal bone mass and changes in the geometric properties of the bone, without alterations in the material properties of the bone tissue. The studied bones, because of the subnormal strength and stiffness, were thus structurally incompetent for sex and age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this adaptive responsed to caloric restriction would be predicted to be deleterious to bone status. In fact, previous studies performed in our laboratory showed impaired mechanical femoral competence in ND rats that may result from altered bone mass and architectural distribution rather than its intrinsic quality, a suggestion supported by the high correlation found between bone mineral content and bone mineral density v. body weight, and ultimate load and yielding load v. moment of inertia [16,17].…”
Section: Introductionmentioning
confidence: 71%
“…Semelhantemente, foi demonstrado por Boyer et al 20 em cujo estudo o peso femoral também sofreu diminuição com o déficit nutricional. É conhecido que a desnutrição ocorrida durante essas importantes fases do desenvolvimento provoca, em ratos, falha na recuperação óssea completa ao menos até os 100 dias de vida 21 e até os 6 meses de vida em humanos 22 .…”
Section: Discussionunclassified